A liveable future is possible confronting the threats to our survival - Chomsky, Noam 1928- (Haymarket Books, 2024)
"A sweeping yet penetrating collection of interviews with Noam Chomsky, exploring the most pressing global concerns of our time. In these illuminating interviews conducted by C.J. Polychroniou, Noam Chomsky yet again shares his brilliant insights on an array of struggles and challenges facing humanity. A Livable Future Is Possible addresses artificial intelligence and the potential for such programs to surpass humans in cognitive awareness; what lies ahead for a world engulfed in a deadly climate crisis; the rise of neo-fascism internationally, and why we should organize across borders to confront it; the striking similarities between Trump and Biden's foreign policies; and a number of other critical issues gripping the planet. Noam Chomsky has been an incomparable model of moral clarity and intellectual courage during his many decades as a scholar and critic. He is the most cited living scholar. One would be hard-pressed to find a more influential voice than Chomsky’s in the West. A Livable Future Is Possible is not only an urgent and informative resource, it is a call-to-action for those hoping to help carry the torch of one of history’s greatest minds." --
Includes index
Keywords: Chomsky, Noam / Interviews; Chomsky, Noam / Political and social views; Linguists / United States / Interviews; World politics / 21st century; United States / Foreign relations / Moral and ethical aspects; United States / Politics and government; Politique mondiale / 21e siècle; États-Unis / Relations extérieures / Aspect moral; États-Unis / Politique et gouvernement; Interviews